2012
DOI: 10.1016/j.jvs.2011.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytoskeleton and energetic metabolism-related proteins at human abdominal aortic aneurysm sites

Abstract: The present results suggest that an anaerobic metabolic state may be favored further to reduce the expression of cytoskeleton-related proteins. The better knowledge of molecular mechanism involved in AAAs may favor development of new clinical strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
(34 reference statements)
0
27
0
2
Order By: Relevance
“…The differential expression cytoskeleton proteins maybe associated with the development of aneurysms. Several remodeling-related mechanisms, due to the reduction of cytoskeleton-related proteins expression, have been associated with abdominal aortic aneurysm (AAA) formation [16].…”
Section: Cytoskeleton and Siasmentioning
confidence: 99%
“…The differential expression cytoskeleton proteins maybe associated with the development of aneurysms. Several remodeling-related mechanisms, due to the reduction of cytoskeleton-related proteins expression, have been associated with abdominal aortic aneurysm (AAA) formation [16].…”
Section: Cytoskeleton and Siasmentioning
confidence: 99%
“…Modrego et al [23] showed that, at the aneurysmal site, there are changes in the expression level of proteins associated with the cytoskeleton and with the glycolytic pathway. According to these authors, at the AAA site, the amount of some cytoskeleton-related proteins, such as microfibril-associated glycoprotein-4 isotype 1, annexin A5 isotype 1, and annexin A2, was reduced with respect to that found in the controls.…”
Section: Proteomics Studies Of Tissue Secretome and Plasma/serum Abdmentioning
confidence: 99%
“…Therefore, reduction of the amount of these proteins in AAA may promote the presence of intraluminal mural thrombus, which has been associated with AAA ruptures. In the proteomic map obtained by these authors, the expression level of most of the glycolytic enzymes was significantly reduced at the AAA site [23]. Recently, Molacek et al [24] carried out a proteomic analysis of the AAA wall and compared the findings with those of non-dilated wall tissue, i.e.…”
Section: Proteomics Studies Of Tissue Secretome and Plasma/serum Abdmentioning
confidence: 99%
“…Asociación entre polimorfismos y aterosclerosis en pacientes con DM2 40---42 Plaquetas Plaquetas circulantes «disfuncionantes» durante la fase aguda de un síndrome coronario agudo. Aumento de la expresión de la PMCA4 en pacientes hipertensos 43---45 Metabolismo energético Nuevos avances en aneurisma y ventrículo izquierdo de SHR 46,47 DM2 y glitazonas Fibrosis y apoptosis miocárdica atenuados por los agonistas de los PPAR-␣ 48,49 Antialdosterónicos Reducen el procesos fibrótico e inflamatorio en el riñón 51 Quercetina Previene la nefrotoxicidad inducida por antitumorales 52 COX-2 Función renal alterada cuando el número de nefronas está disminuido y existe un aumento en la ingesta proteica 53,54 la insulina plasmática, y por consiguiente la resistencia a la insulina 30 . Aunque tales efectos antioxidantes, antihipertensivos y beneficiosos en la acción insulínica y la función endotelial de estos derivados del chocolate se han documentado en varios estudios, aún queda por consensuarlos en estudios en humanos con un gran número de sujetos.…”
Section: Iecasunclassified
“…Sin embargo, se desconocían los efectos en la célula a nivel estructural, oxidativo y del metabolismo energético en la AAA inducidos por la HTA 46 . En este trabajo sugieren que un metabolismo anaerobio podría favorecer la reducida expresión de proteínas asociadas con el citoesqueleto y, por lo tanto, un mayor conocimiento sobre los mecanismos moleculares en la AAA favorecería el desarrollo de nuevas estrategias en la clínica.…”
Section: Metabolismo Energéticounclassified